Prevalence of Atrial Fibrillation in patients attending emergency department of Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Adhikari, Krishna Prasad; Malla, Rabi; Limbu, Deepak; Rauniyar, Binaya Kumar; Regmi, Sudhir; Hirachan, Anish; BHatt, Yadav (Nepalese Heart Journal, 2016)
Background and Aims: Atrial fibrillation (AF) is the most common sustained arrhythmia. This study aims to evaluate its prevalence in patients attending emergency department of tertiary care cardiac centre. Methods: It was a prospective observational study of 1012 consecutive patients who attended emergency department of Shahid Gangalal National Heart Centre from September 2014 to November 2014. Electrocardiogram, demographic features, diagnosis and clinical presentations were reviewed. Results: Among the 1012 patients, 553 (54.6%) were male and 459(45.4%) were female. Mean age was 52.13} 17 years. A total of 140 patients (13.8%) patients had AF. The mean age of patients with AF was 55 years. The prevalence of AF was higher in female than male (19.2% Vs 9.4%). Among the Rheumatic heart disease patients, seventy percentages of them had AF. Dyspnea was the commonest symptom of patients with AF followed by palpitation. Conclusion: The prevalence of AF in our study is higher than in western world mainly because of endemic rheumatic heart disease. Nepalese Heart Journal 2016; 13(1): 1-4